THE EFFECT OF PLYOMETRICS TRAINING ON ATTENTION LEVEL AMONG MEDICAL STUDENTS - Mahardika Budjana Sultan Ilham; Muhammad Mufaiddudin; Bagaskara Yogatama; Ainun Rahmasari Gumay; Darmawati Ayu Indraswari; Yuriz Bakhtiar (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2019)
Introduction: Plyometrics are a popular form of physical exercise that plays an important role on the improvement of athlete’s performance, such as agility and muscle power. However, the effect of plyometrics training on neurocognitive function has not been studied yet. The aim of this study was to analyze the effect of plyometrics training on attention level among medical students. Methods: A quasi experimental study with pre and post-test with control group design. The subjects were 36 male students in Faculty of Medicine, Diponegoro University with range of age 15 to 25 years old. Subjects were divided into 2 groups: C (control group) and EP (experimental group). The EP group undergone plyometrics training for 6 weeks. Each week consists of 2 sessions exercise with 5 movements every session. The indicator of examination was attention level using Attention Networks Test. It was measured before training and after 6 weeks of training. Results: A significant improvement of attention function was found in alerting, orienting, and executive function after plyometrics training for 6 weeks with p<0,001. After 6 weeks of plyometrics training, there was an improvement of alerting function in EP group with median 77,7 (49,8 – 111,1) ms to 58,45 (4,9 – 90,4) ms, improvement of orienting function with median 24,45 (2 – 89,3) ms to 19,2 (-0,3 – 88,8) ms, and executive function with median 74,1 (39,8 – 220,8) ms to 49,2 (-21 – 102,1) ms. Conclusion: Plyometrics training for 6 weeks can improve attention level among medical students.Keywords: attention level; attention network test; plyometrics training